PENGARUH STRUKTUR KEPEMILIKAN DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Noviatara Dwi Putri; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2013)
This research aims to analyze the effects of ownwership structure and audit quality on earning management of manufacturing sector in Indonesia’s companies The sample in this study were manufacturing sector companies listed in Indonesian Stock Exchange (IDX) in the periode 2009-2011. The number of sample used were 39 companies listed were taken by purposive sampling. The analysis method of this research used multiple linear regression analysis. The result of this research showed that ownership of managerial and audit firm size had negative and significant influence to earning management; meanwhile ownership of institutional, auditor independence and industry specialization auditor had not significant effect to earning management.